A preliminary fertilization test on sorghum (Sorghum bicolor L. Moench) with three organic amendments of humus and domestic wastes - Guerrero-Cabrera, Luis; UNIVERSIDAD DEL PAPALOAPAN (2019)
Organic amendments like compost are used as an alternative to diminish soil damages caused by chemical fertilization. Compost contains nutrients and microbial communities with some beneficial bacteria and fungi for the plant. A study was carried out in order to assess the effectiveness of compost on sorghum (Sorghum bicolor L. Moench). Compost and fermented organic amendments were produced for 60 days with domestic wastes and humus of plant debris from agriculture and gardening in polyethylene bioreactors of 200 L. A fertilization test was applied under randomized block design with one factor (fertilization treatment) to one-month-age sorghum plants in a land plot. Plant height and fresh weight variables were recorded and analyzed by ANOVA and Tukey test (p ≤ 0.05) at the end of three-months period. Results showed that plant height and fresh weight were higher in plants fertilized with compost than those fertilized with control (chemical fertilizer) and fermented organic amendments (p £ 0.05). Vegetable domestic wastes and humus are a good option as substrate to produce compost due to their high availability and low cost.